Design and Building A 2D Game as Educational Media for The Babad Pasirluhur Folklore Using Construct 3 - Chevin, Virginawan Alessandro; Permadi, Dimas Fanny Hebrasianto (Journal of INISTA, 2024)
Folklore can also be called a part of Indonesian culture that tells about entertainment, history and culture from a region in Indonesia. Indonesian folklore has educational value and cultural elements that can be studied. One way of learning about folklore can be implemented through games. Games can be used as an educational media because apart from producing information they can also be entertainment for those who play them. Based on the background, we have conducted interviews with teachers at Public Elementary School 2 Purwokerto Lor and obtained results regarding the need for media to introduce folklore. In this elementary school, the folklore about Babad Pasirluhur is not yet understood by students. So we propose to design a 2D game as an educational media for the Babad Pasirluhur folklore implemented into adventure genre. Therefore, the aim of this research is to design an educational adventure game for the Babad Pasirluhur folklore using the Game Development Life Cycle (GDLC) method. This game was build using the Construct 3 game engine because suitable for simple adventure game. The resutls obtained were that black box method functional with a success score of 100% from 5 testers. Meanwhile, the UAT test obtained results of 84,7% from 33 grade 4 students at Public Elementary School 2 Purwokerto Lor. The UAT test results stated that it was included in the “strongly agree” category. These results have been tested using the normality test and one sample t-test and the concluesion is that H0 is rejected and H1 is accepted. So the results of this game can be accepted as a learning media for the Babad Pasirluhur folklore by grade 4 students at Public Elementary School 2 Purwokerto Lor. Suggestions for further development are needed to improve the design to suit the character of grade 4 students based on the results of the UAT testing on the design section which got the lowest score is 84%.